2014
DOI: 10.1080/01621424.2014.968502
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Student Interprofessional Education (IPE) Training for Team-Based Geriatric Home Care: Does IPE Training Change Students’ Knowledge and Attitudes?

Abstract: Our study assesses changes in students' knowledge and attitudes after participation in an interprofessional, team-based, geriatric home training program. Second-year medical, physician assistant, occupational therapy, social work, and physical therapy students; third-year pharmacy students; and fourth-year dental students were led by interprofessional faculty teams. Student participants were assessed before and after the curriculum using an interprofessional attitudes learning scale. Significant differences an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 6 publications
1
74
0
4
Order By: Relevance
“…The length of training time was also an important factor in the IPE effect. Two studies involved students trained for one year 31 or more than half a year 25 . However, Sigalet et al studied three‐hour training, 20 and Bradley et al studied three‐month training 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The length of training time was also an important factor in the IPE effect. Two studies involved students trained for one year 31 or more than half a year 25 . However, Sigalet et al studied three‐hour training, 20 and Bradley et al studied three‐month training 26 .…”
Section: Discussionmentioning
confidence: 99%
“…These are important findings because RACF can meet some of the pressure to provide IPE experiences for students, offering an alternative to the traditional settings for IPE, namely Stroke and Palliative Care Unit placements or the logistically and financially challenging student led wards. With the evidence that residents benefit from such interactions, all groups gain when RACF become a learning centre (Elliott, Annear, Bell, Palmer, & Robinson, 2015;Reilly et al, 2014;Seaman, Bulsara, & Saunders, 2014). For example, a cross-sectional study by Ross, Duigan, Boyle, and Williams (2014) found relatively similar ASD subscale scores for paramedic students to the scores of students in this study.…”
Section: Discussionmentioning
confidence: 89%
“…Only one study was published in 1981 and the other 6 were published between 2012 and 2015 indicating the recently increasing interest in research in this area. All publications originated from the United States . Three originated from the same centre, University of Alabama at Birmingham Geriatric Education Center, with 2 of them reporting on the same training experience and sample .…”
Section: Resultsmentioning
confidence: 99%
“…Geriatric outreach facilities (i.e. nursing homes) were the main teaching venue in all studies where undergraduate students were involved, while faculty members were trained within University locations …”
Section: Resultsmentioning
confidence: 99%